Bisnis Dalam Islam - Ariyadi Ariyadi (Jurnal Hadratul Madaniyah, 2018)
Islam regulates all human activities including in doing muamalah by providing restrictions on what can be done and what is not allowed. In sharia business, the business must be based on sharia. All laws and rules are done to keep businessmen to get a lawful fortune and in ridhai by Allah SWT and the realization of equal distribution of welfare. Then ethics or rules about sharia business have an important role also in syari'ah-based business. The essence of business in Islam besides seeking material gain is also seeking immaterial benefits. The immaterial advantage is the profit and happiness of ukhrawi. It is in this context that the Qur'an offers an advantage with a business that never recognizes the harm which the Qur'an termed the "lan tabura". Because even if materially Muslim businessmen lose money, but in essence he remains lucky to get reward for his commitment in running a business in accordance with sharia.